International Perspectives on Literacy Learning with iPads. Issue 3 (October 2015) - Gallagher, Tiffany L.; Fsher, Douglas; Lapp, Diane; Rowsell, Jennifer; Simpson, Alyson; Scott, Ruth Mcquirter; Walsh, Maureen; Ciampa, Katia; Saudelli, Mary Gene
This article profiles the use of the iPad (a tablet) in classroom literacy activities in three different instructional environments in different parts of the world: Toronto, Canada; San Diego, United States; and Sydney, Australia. This two-year, qualitative study included observational fieldwork filming students' interactions with tablets in the midst of literacy events. Students in each context used the iPads to make meaning, with the participating classroom teachers affording their students some degree of self-determination with respect to technology use. We describe these three instructional environments and illustrate how these diverse landscapes reflected a variety of ecologies or models that contributed inherently to the nature of learning on the iPads. We describe our findings that show how context and environment allow for different kinds of learning and that may elucidate the array of learning potential afforded with this device.